Enhancing the Strength of Black Cotton Soil with Enzyme and Industrial Waste - Ankit Kumar Yadav*; Anil Kumar; S.K. Madan (International Journal of Environmental Planning and Development Architecture, 2023)
Expansive soils are troublesome and prone to ground movements, which can cause substantial damage to underlying buildings as well as a loss in bearing capacity. Moisture fluctuation activates the expansive character of soils, causing it to swell and shrink. This has long been known in geotechnical engineering. To treat expansive soils, a variety of stabilizing additives such as lime, cement, and fly ash have been employed. In recent years the use of bio-enzymes as a soil stabilizing agent has shown a great potential in soil stabilization. The strength and endurance of enzymatic stabilization of expanding soils in road pavements are investigated in this work. Several tests were carried out to determine the strength and durability of stabilized soil. The test results indicated that Black cotton soil attained a maximum dry density when mixed with 15% FA. The density attained satisfied for the construction of embankments of 3m and 5m height (MoRTH and MoRD), similarly it can be used as subgrade in the construction (>16.5kN/m3) of rural roads as per MoRD specifications. Also, the value of CBR increased to 25% when mixed with 15% FA. Similarly, when BC soil was mixed with 0.0025% Roadezyme and 15% Fly ash the MDD was increased to 16.87kN/m3 with a concluding remark as it is effective in soil stabilization. Results also indicated that unconfined compressive strength of BC soil on addition with Roadezyme increased to 53% for 7days and 35% for 28days curing period. The use of an enzyme-based stabilizer significantly enhanced the strength of BC soils, demonstrating its capacity to preserve material stiffness despite moisture fluctuations.
Keywords: CBR; UCS; black cotton soil; fly ash; roadezyme